THE URGENCY OF DONATED LAND CERTIFICATION IN SAMPANG REGENCY OF MADURA - Moh. Wardi (Faculty of Sharia IAIN Madura collaboration with The Islamic Law Researcher Association (APHI), 2016)
Abstract:People donated their property such as lands or buildings because of charity of their selfand familyand for the sake of hereafter investment. However, there some obstacles faced to certify the given donated land, particularly in terms of administration and finance. The purpose of this research is to identify and explain the urgency, problems, and alternative solutions concerning the donated land certification in Sampang subdistrict. The research method used in this research was qualitative research with a focus on phenomenological research type. The data was obtained through interview and observation. Then, the data was analyzed by using data reduction, data display or data presentation, and data conclusion. The informants in this research were people in Sampang subdistrict consisting of 20 people. The research findings showed: The first, people donated their property because of charity of their self and family. Landsor buildings were registered to have a donatedland certificate in order to avoid an accusation from the heir of the land or building being donated in the future. The second, the famous phenomenon and problem in donation (waqf) were that the process of donated land submission conducted by a wâqif [a person who donated the land or the building] to a nâdzir [a committee or person who who received the donation] without the approval of wâqif heirs. In addition, the service was different in terms of administration and the amount of money should be paid from a donated and non-donated land certification in National Land Affairs Agency (BPN). The third, the alternative solution which is provided was thatthe submission of donated property is not enough to doonly through verbal agreement, but this wassuggested to that wâqif and nâdzir had to sign an official agreement or memorandum of understanding (MoU). When the required documents of certifying the donated property was not proceeded yet by or they lasted very long in in PPAIW and BPN, the relevant action that should be taken wasto clarify what the prime problem are to the PPAIW and BPN officer. Key Words:certification, donated land, wâqif, nâdzir Abstrak:Masyarakat mewakafkan harta bendanya berupa tanah dan atau bangunannya karena semata-mata amal jariyah diri dan keluarga untuk investasi akhirat. Namun, dalam rangkaian prosesnya, ia menuai problem yang menghambat proses sertifikasi tanah wakaf, di antaranya adalah masalah administrasi dan pembiayaan. Tujuan penelitian ini adalah untuk mengetahui dan menjelaskan problem, dan solusi alternatif tentang sertifikasi tanah wakaf di Kecamatan Sampang. Metode yang digunakan dalam penelitian ini adalah kualitatif dengan jenis penelitian fenomenologis. Data diperoleh dari hasil wawancara dan observasi. Selanjutnya, analisis data dilakukan dengan reduksi data, display atau penyajian data, dan tahap kesimpulan. Informan dalam penelitian masyarakat Kecamatan Sampang yang terdiri atas 20 wâqif. Hasil penelitian menunjukan: Pertama, masyarakat mewakafkan harta bendanya karena semata-mata amal jariyah diri dan keluarga. Tanah/bangunan didaftarkan sertifikat tanah wakaf supaya tidak ada gugatan di kemudian hari dari ahli waris. Kedua, fenomena dan persoalan yang lazim dalam perwakafan, bahwa pada saat penyerahan tanah wakaf oleh wâqif kepada nâdzir tanpa persetujuan dari calon ahli waris wâqif. Selain itu, ada versi yang berbeda di masyarakat tentang pelayanan, frekuensi administrasi, dan nominal biaya antara tanah wakaf dan non wakaf di BPN. Ketiga, solusi alternatifnya, bahwa penyerahan harta wakafnya tidak cukup melalui lisan/perkataan, namun dengan perjanji-an/MoU. Langkah-langkah yang paling relevan ketika berkas mengendap/lama di PPAIW dan BPN yaitu menindak lanjuti akar persoalannya ke PPAIW dan BPN.